[OP.8A.09] EFFICACY OF MONOCLONAL ANTIBODIES ANTI-PROPROTEIN CONVERTASE SUBTILISIN-KEXIN TYPE 9 IN IMPROVING LIPID PROFILE AND ARTERIAL STIFFNESS IN PATIENTS AFFECTED BY FAMILIAL HYPERCHOLESTEROLEMIA. (September 2017) - Mandraffino, G.; Aragona, C.O.; Cairo, V.; Trapani, G.; Quartuccio, S.; Mamone, F.; Scuruchi, M.; Saitta, A.; Imbalzano, E.
Abstract : Objective: monoclonal antibodies that inhibit proprotein convertase subtilisin-kexin type 9 (PCSK9), have emerged as a new class of drugs that effectively lower LDL cholesterol levels. Hypercholesterolemic patients present early signs of vascular inflammation and damage. We investigate whether after six months of treatment with anti-PCSK9 monoclonal antibodies we can find any improvement of pro-atherogenic profile and of arterial stiffness (AS) in patients affected by familial hypercholesterolemia already in treatment with the maximally tolerated statin therapy. Design and method: We enrolled 34 people who had decided to start treatment with anti-PCSK9 drugs; of these, 32 have completed the 6-months observation period. At enrollment and 6 months later we evaluated anthropometrics, laboratory profile, pulse wave velocity (PWV) and carotid intima-media thickness (cIMT). Results: After 6-months of treatment we found a significant decrease of inflammatory markers (Hs-CRP: −46.5%; Fibrinogen: −18.9%), LDL-C and lipoprotein (a) levels (respectively −65.9% and −34.2%). PWV (−9.5%) appeared to be improved; cIMT remained unchanged. PWV reduction appeared to be correlated with fibrinogen and LDL-C reduction. However, reduced PWV appeared to be not dependent on LDL-C and fibrinogen by the multiple regression analysis. Conclusions: After 6 months of treatment with monoclonal antibodies anti-PCSK9 the levels of CRP, Fibrinogen, LDL-C, and Lp (a), as well AS indices, are significantly improved as compared to baseline. We report the important evidence that a treatment with anti-PCSK9 monoclonal antibodies may improve significantly the arterial stiffness in patients affected by familial hypercholesterolemia.